SEORANG PENDERITA SINDROM NEFRITIK AKUT PASCA INFEKSI STREPTOKOKUS - Renny A Rena, Ni Made; Suwitra, Ketut (journal of internal medicine, 2009)
Acute nephritic syndrome is classically de! ned by symptoms of oliguria, oedem, hypertension and also urinalysisabnormality such as proteinuria less than 2 grams/day, hematuria, or ! nding of erytrocite silinder in the urine. The etiology ofacute nephritic syndrome are disorders of primary glomerulopathy (idiopathic), glomerulopathy after infection, DisseminatedLupus Erythomatosus (DLE), vasculitis and hereditary nephritis (Alport syndrome). Acute nephritic syndrome is one of clinicalmanifestation of acute glomerulonephritis after streptococcal infection, which is in